Synthesis, Characterization and Anti-inflammatory-Analgesic Properties of 6-(α-Amino-4-chlorobenzyl)thiazolo [3,2-b]-1,2,4-triazol-5-ols - Tozkoparan, Birsen; Gökhan, Nesrin; Küpeli, Esra; Yeşilada, Erdem; Ertan, Mevlüt (Arzneimittelforschung, 2004)
A series of 6-(a-amino-4-chlorobenzyl)-thiazolo[3,2-b]-1, 2, 4-triazol-5-ols (2a-j) were synthesized from 6-(4-chlorobenzyl idene) thiazolo [3,2-b]-1, 2, 4-triazolo-5(6H)-one (2) by applying Michael addition reaction. All the compounds were characterized by their melting points, ele mentary analysis, IR and 1H-NMR spectra and screened for their anti-inflamma tory and analgesic activities. Among the derivatives compound 2i bearing 4-(4-acetylphenyl)piperazine showed the highest and dose-dependent analgesic and anti-inflammatory activity without inducing any gastric lesion.
Keywords: 6-(α-Amino-4-chlorobenzyl) thiazolo [3,2-b]-1, 2, 4-triazol-5-ols,; anti-inflammatory and; analgesic activities, mouse, synthesis